B. Sobolewska, M. Sobolewski, Myśl polityczna XIX i XX w. Liberalizm. Warszawa 1978 - Zmierczak, Maria (Czasopismo Prawno-Historyczne, 1979)
Recenzja: Barbara Sobolewska, Marek Sobolewski, Myśl polityczna XIX i XX w. Liberalizm, Warszawa 1978, PWN, ss. 601.